Indications for Intravenous T3 and T4 - Feldkamp, Jasper David; Feldkamp, Joachim (Hormone and Metabolic Research, 2024)
Therapy with thyroid hormones normally is restricted to substitution therapy of patients with primary or secondary hypothyroidism. Typically, thyroid hormones are given orally. There are few indications for intravenous use of thyroid hormones. Indications for parenteral application are insufficient resorption of oral medications due to alterations of the gastrointestinal tract, partial or total loss of consciousness, sedation in the intensive care unit or shock. In almost all cases, levothyroxine is the therapy of choice including congenital hypothyroidism. In preterm infants with an altered thyroid hormone status, studies with thyroid hormones including intravenous liothyronine showed a normalisation of T3 levels and in some cases an amelioration of parameters of ventilation. A benefit for mortality or later morbidity could not be seen. Effects on neurological improvements later in life are under discussion. Decreased thyroid hormone levels are often found after cardiac surgery in infants and adults. Intravenous therapy with thyroid hormones improves the cardiac index, but in all other parameters investigated, no substantial effect on morbidity and mortality could be demonstrated. Oral liothyronine therapy in these situations was equivalent to an intravenous route of application. In myxoedema coma, intravenous levothyroxine is given for 3 to 10 days until the patient can take oral medication and normal resorption in the gastrointestinal tract is achieved by restoring at least peripheral euthyroidism. Intravenous levothyroxine is the standard in treating patients with myxoedema coma. A protective effect on the heart of i.v. levothyroxine in brain-dead organ donors may be possible.
Keywords: thyroid; hypothyroidism; liothyronine; levothyroxine; triiodothyronine